Effectiveness of hydrogen peroxide wipes for surface disinfection in healthcare facilities - Lopuzzo, Marco; Montagna, Maria Teresa; Triggiano, Francesco; Caggiano, Giuseppina (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Introduction. The correct method of surface disinfection in hospitals is an essential tool in the fight against the spread of healthcare-associated infections caused by multi-resistant microorganisms. Currently, there are many disinfectants on the market that can be used against different microorganisms. However, the effectiveness of different active molecules is controversial in the literature.Study design. The aim of this study was to evaluate the effectiveness of wipes based on hydrogen peroxide (1.0%) and highly specific plant-based surfactants, contained in H2O2TM (Hi-speed H2O2TM) products, against some hospital-associated microorganisms.Methods. The effectiveness of the wipes was tested against nosocomial and control strains of methicillin-resistant Staphylococcus aureus, carbapenem-resistant Pseudomonas aeruginosa, Klebsiella pneumoniae carbapenemase, Aspergillus fumigatus and Candida parapsilosis. Specifically, in vitro activity was assessed using three different techniques: stainless steel surface testing, surface diffusion testing and well diffusion test.Results. The three different methods tested confirm the wipes’ good effectiveness against the most common multi-resistant bacteria and against fungi.Conclusions. These data show that the tested wipes could be a valid adjunct to the disinfection process and could assist in the prevention of healthcare-associated infections.